Kontroversi Reklamasi Pantai Ancol: Manfaat Ekonomi vs Kerusakan Lingkungan - Sahliah Dita Arzikah; Yudha Arya Permana (Journal of Citizenship, 2023)
AbstractTourism areas in Indonesia are of course very diverse and can be enjoyed by all groups, especially in the DKI Jakarta area, namely Ancol Beach. Ancol Beach is a beach located in North Jakarta with a beach area of 6.5 km which is divided into several areas, including Ancol Carnival Beach, Lagun Beach, Ancol Festival Beach, Ria Ancol Beach, Ancol Mariana Beach, Ancol Beautiful Beach, and Bende Beach. The need for land for tourism in Jakarta has made the government want to reclaim Ancol beach. However, the pros and cons of Ancol beach reclamation raises a question, will this have a negative impact on the environment or a positive impact on the regional economy? Based on the results of the study, the issuance of a reclamation permit has the potential to damage the environment, especially in the coastal waters around Ancol, due to dredging materials for reclamation land there are activities to take sand material so that the aquatic ecosystem is further destroyed. When viewed from economic factors, it increases local revenue from the tourism sector. Which is where this reclamation will be the biggest and best tour in Asia, not just in Indonesia.Keyword: Reclamation, Environment, Economy AbstrakKawasan pariwisata di Indonesia tentu sangat beragam dan dapat dinikmati oleh semua kalangan, khususnya di daerah kawasan DKI Jakarta yakni Pantai Ancol. Pantai Ancol merupakan pantai yang berlokasi di Jakarta Utara dengan luas pantai sebesar 6,5 km yang terbagi menjadi beberapa kawasan, diantaranya pantai karnaval ancol, pantai lagun, pantai festival ancol, pantai ria ancol, pantai mariana ancol, pantai indah ancol, dan pantai bende. Kebutuhan akan lahan untuk pariwisata di Jakarta membuat pemerintah ingin mereklamasikan pantai ancol. Namun adanya pro serta kontra terhadap reklamasi pantai ancol membuat timbual sebuah pertanyaan, apakah ini berdampak negatif untuk lingkungan atau berdampak positif untuk perekonomian daerah? Berdasarkan hasil penelitian, dengan diterbitkannya izin reklamasi ini memiliki potensi merusak lingkungan terutama dikawasan perairann peisisr sekitar ancol, dikarenakan untuk bahan pengerukan lahan reklamsi terdapat kegiatan pengambilan material pasir sehingga semakin hancurnya ekosistem perairan. Jika dilihat dari faktor ekonomi menambah pendapatan asli daerah dari sektor pariwisata. Yang dimana reklamasi ini akan diajdikan wisata terbesar dan terbai se-Asia bukan hanya se-Indonesia.Kata kunci: Reklamasi, Lingkungan, Ekonomi